Reliability of mental capacity assessments in psychiatric in-patients - Ruth Cairns; Clementine Maddock; Alec Buchanan; Anthony S. David; Peter Hayward; Genevra Richardson; George Szmukler; Matthew Hotopf (2005)
Previous work on the reliability of mental capacity assessments in patients with psychiatric illness has been limited.To describe the interrater reliability of two independent assessments of capacity to consent to treatment, as well as assessments made by a panel of clinicians based on the same interview.Fifty-five patients were interviewed by two interviewers 1-7 days apart and a binary (yes/no) capacity judgement was made, guided by the MacArthur Competence Assessment Tool for Treatment (MacCAT-T). Four senior clinicians used transcripts of the interviews to judge capacity.There was excellent agreement between the two interviewers for capacity judgements made at separate interviews (kappa=0.82). A high level of agreement was seen between senior clinicians for capacity judgements of the same interview (mean kappa=0.84).In combination with a clinical interview, the MacCAT-T can be used to produce highly reliable judgements of capacity.